Hunger and salary from the point of view of social medicine - Arias Segovia, Mesías (1968)
The study was conducted in the neighborhood of 706 families Collique. Formerly a family record was drawn to follow the survey system, having found a low monthly fee 25.20%, ranging from 200 to 1.500 soles. The per capita income per day in 45.63% of families are highly insufficient, S /. 1.00 to S/.15.00. On the other hand 76.56% of families live exclusively wage of the household head.